Centrifugation versus PureGraft for fatgrafting to the breast after breast-conserving therapy - Mestak, Ondrej; Sukop, Andrej; Hsueh, Yu-Sheng; Molitor, Martin; Mestak, Jan; Matejovska, Jana; Zarubova, Lucie (World journal of surgical oncology, 2014)
BACKGROUND: Breast-conserving treatment (BCT) leads to a progressive and deteriorating breast deformity. Fatgrafting is ideal for breast reconstruction after BCT. The most frequently utilized technique for fat processing is centrifugation. The PureGraft device (Cytori Therapeutics, San Diego, CA, USA) is a new method that involves washing and filtering the fat to prepare the graft. We compared the subjective and objective outcomes of two fat-processing methods, centrifugation and PureGraft filtration. METHODS: Thirty patients underwent breast reconstruction performed by a single surgeon (OM) after BCT in our department between April 2011 and September 2012. The patients were preoperatively divided into two groups randomly: 15 received fatgrafts processed by centrifugation, and 15 received fatgrafts processed by washing in PureGraft bags. The patients were followed up for 12 to 30 months. To measure the subjective outcome, we distributed the BREAST-Q questionnaire to all the patients both preoperatively and 1 year postoperatively. The BCCT.core software evaluated the objective outcome of breast reconstruction by fatgrafting. RESULTS: The Breast-Q results indicated a tremendous improvement in the modules "Satisfaction with Breast" and "Psychosocial Well-being". The "Sexual Well-being" scale also improved. Only the module "Satisfaction with Breasts" significantly differed between groups; patients treated with the PureGraft fat exhibited better outcomes. The BCCT.core results did not significantly differ between the groups. CONCLUSION: One year postoperatively, the outcomes of the use of PureGraft bags or centrifugation to process fat for breast reconstruction after BCT did not differ. The unpredictability of the results following fatgrafting procedures is likely due to interindividual differences with yet-undisclosed causes.
Keywords: dospělí; nádory prsu; Mammaplasty; průzkumy a dotazníky; Female; Adult; Centrifugation; ženské pohlaví; Surveys and Questionnaires; lidé; Mastectomy, Segmental; podkožní tuk; Breast Neoplasms; Subcutaneous Fat; centrifugace; následné studie; prognóza; filtrace; segmentální mastektomie; Follow-Up Studies; Prognosis; lidé středního věku; Filtration; mamoplastika; Middle Aged; Humans